I-V characteristics observation of graphene boron nitride vertical heterojunction van der waals resonant tunneling diode - Ahmed, Saber; Sobhan, Rifat Binte (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.